Eikenella corrodens from a brain abscess - Karunakaran, Rina; Marret, Mary Joseph; Hassan, Hamimah; Puthucheary, S.D. (College of Pathologists, Academy of Medicine Malaysia, 2004)
A 2-year-old boy with underlying congenital cyanotic heart disease presented with seizures and fever and was found to have bilateral parietal cerebral abscesses. Drainage of the pus from the abscesses was done in stages; on the day of admission, four days after admission and 3 weeks after admission. Although the pus from the first drainage did not grow any organisms, the pus from the second drainage on the fourth day of admission yielded a mixed growth of Eikenella corrodens and Streptococcus milleri. Following the second drainage of pus, the child was noted to have mild weakness (grade 3/5) and increased tone in the left upper limb. Three weeks after admission, due to recurring fever, further neurological signs and findings of an enlarging right cerebral abscess on a repeat CT scan, a third drainage was carried out. However no growth was obtained from this specimen. This patient was managed both surgically and with appropriate antibiotics. Over the next four months, serial CT scans revealed gradual resolution of the abscesses with disappearance of the surrounding oedema. The child showed gradual recovery of his left sided weakness with resolution of tone and reflexes to normal.